Health literacy among older adults in Portugal and associated sociodemographic, health and healthcare-related factors - Costa, A. S.; Feteira-Santos, R.; Alarcão, V.; Henriques, H.; Madeira, T.; Virgolino, A.; Arriaga, M.; Nogueira, P. J. (International Journal of Environmental Research and Public Health, 2023)
Although the health literacy level of the general population was described recently, little is known about its specific levels among older adults in Portugal. Therefore, this cross-sectional study aimed to investigate the levels of health literacy demonstrated by older adults in Portugal and explore associated factors. Using a randomly generated list of telephone numbers, adults aged 65 years or more living in mainland Portugal were contacted in September and October 2022. Sociodemographic, health and healthcare-related variables were collected, and the 12-item version of the European Health Literacy Survey Project 2019–2021 was used to measure health literacy. Then, binary logistic regression models were used to investigate factors associated with limited general health literacy. In total, 613 participants were surveyed. The mean level of general health literacy was (59.15 ± 13.05; n = 563), whereas health promotion (65.82 ± 13.19; n = 568) and appraising health information (65.16 ± 13.26; n = 517) were the highest scores in the health literacy domain and the dimension of health information processing, respectively. Overall, 80.6% of respondents revealed limited general health literacy, which was positively associated with living in a difficult household financial situation (4.17; 95% Confidence Interval (CI): 1.64–10.57), perceiving one’s own health status as poorer (7.12; 95% CI: 2.02–25.09), and having a fair opinion about a recent interaction with primary healthcare services (2.75; 95% CI: 1.46–5.19). The proportion of older adults with limited general health literacy in Portugal is significant. This result should be considered to inform health planning according to the health literacy gap of older adults in Portugal.